Impact of Omega-3 Fatty Acid Supplementation on Cardiovascular Health - Muiti, Benard (American Journal of Food Sciences and Nutrition, 2024)
Purpose: The aim of the study was to investigate the impact of omega-3 fatty acid supplementation on cardiovascular health. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: Omega-3 fatty acid supplementation has a positive impact on cardiovascular health by reducing the risk of heart attacks and strokes, lowering blood pressure, improving lipid profiles, and providing anti-inflammatory and anti-arrhythmic effects. It is particularly beneficial for individuals with heart conditions. However, dosages matter, and individual health factors should be considered before starting supplementation. Implications to Theory, Practice and Policy: Inflammation theory, lipid theory and platelet aggregation theory may be use to anchor future studies on the impact of omega-3 fatty acid supplementation on cardiovascular health. Develop and update clinical guidelines that provide clear recommendations for healthcare practitioners regarding the appropriate use of Omega-3 fatty acid supplementation in various patient populations. Regulation and Quality Control: Advocate for stringent regulation and quality control measures within the supplement industry.